Analysis of the technological impact on industry and its effects on waste production and disposal: a case study of the surfboard manufacturing industry - Barcelos, Ricardo Luis; Magnago, Rachel Faverzani; Leripio, Alexandre Avila (Ciência e Natura, 2018)
Cleaner Production (CP) advocates the application of preventive and integrated strategies to processes products minimizing the generation of waste and pollution. However, not always technological innovations in production bring with it an improvement for CP. The surfboard industry has been dismissive of CP. Studies revealed a concentration of the production residues on the manufacturers due to the vertical process of the production stages. Nonetheless, the incorporation of machining technology of the polyurethane blocks through Computerized Numerical Control (CNC) led to a horizontal process. The aim of this study was to map the current process, identifying the major waste producers, and detailing management for these wastes. A case study was carried out to examine the surfboard industry. The survey revealed that the links of the production chain can be accomplished by the diverse actors participating in the manufacturing industry. However, the largest amount of waste is produced by big manufacturing industries rather than small, outsourced companies. It became clear that the introduction of CNC technology was responsible for the centralization of waste production, previously distributed among all manufacturers. Technological innovation had no impact on the reduction or reuse of waste or even a better management of its disposal.